Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in China. (14th May 2013) - Cui, Zhenling; Yue, Shanchao; Wang, Guiliang; Meng, Qingfeng; Wu, Liang; Yang, Zhiping; Zhang, Qiang; Li, Shiqing; Zhang, Fusuo; Chen, Xinping
Abstract: Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas (GHG) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system (HY) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop (CC) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1, which is only 38% more N fertilizer input than that applied in the CC system. Both the N2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.